Distinction and omnivorousness in tourists' food consumption. (October 2019) - Lin, Jiayi; Cui, Qingming; Marin, Jaume; Xu, Honggang
Highlights: The distinctive and omnivorous tastes in food coexist in tourism context, but in different tourist groups. The snobbish tourists legitimize exotic food as a distinctive taste while disregarding familiar food as legitimate food. The omnivorous tourists hold an inclusive attitude towards exotic and familiar foods for many utilitarian purposes. The research has implications for studying cultural tastes of tourist class, and destination management. Abstract: This study investigates tourists' cultural tastes in food by applying the sociological theory of cultural distinction and omnivorousness. The consumption of food by Chinese tourists in their travels across Spain is analyzed, with the fieldwork being conducted in Spain. Semi-structured interview was used to collect data about tourists' food tastes. The results show that distinctive and omnivorous tastes in food coexist, but differently across tourist groups. Snobbish tourists regarded exotic food as distinctive and legitimate, and undervalued familiar food. Omnivorous tourists held a more equal and inclusive attitude towards both exotic and familiar foods. The omnivorous tourists' openness to familiar food involved many utilitarian purposes. The research results have implications for future research on cultural tastes of tourist class, and destination marketing and management.